Alternate HPLC method for the analysis of tetrabutylammonium hydroxide in [18F]fluorodeoxythymidine (FLT). Issue 13 (9th August 2017) - Poon, Jackson; Katsifis, Andrew; Fulham, Michael
ABSTRACT: Tetrabutylammonium hydroxide is a common reagent used in the synthesis of [ 18 F]Fluorodeoxythymidine (FLT) for positron emission tomography imaging. The British Pharmacopeia monograph for the analysis of [ 18 F]FLT was released in 2015 incorporating a HPLC method for the analysis of tetrabutylammonium hydroxide. We describe alternate HPLC conditions that mitigate the challenges in fulfilling the system suitability requirements such as signal to noise and symmetry factor that are specified in the monograph. Our method was validated by analyzing tetrabutylammonium hydroxide at a range of concentrations to determine the linearity ( R 2 = 0.994), accuracy (≤9.2%) and precision (≤3.2%). Our method does not affect the analysis of [ 18 F]FLT and it complies with all requirements in the BP monograph. GRAPHICAL ABSTRACT: